Maori art market 2011. - Toi Māori Aotearoa (Organization) (Wellington : Toi Maori Aotearoa, 2011)
MAORI ART MARKet is an iconic biennial event produced by Toi Maori Market Limited a subsidiery of Toi Maori Aotearoa. This year's Market was held from the 6th-9th of October 2011 at Pataka Museum and Gallery and Te Rauparaha Arena in Porirua City, Wellington. MAORI ART MARKet 2011 brought together over 200 Maori visual artists, musicians and culinary experts. MAORI ART MARKet showcases the best contemporary Maori art under the same roof for three days. Members of the public can view the best that Aotearoa has to offer, as well as having the opportunity to purchase works for themselves. In addition to the art works for sale, there is an extensive public programme that features fashion, cooking, music and other things to keep the audience entertained.
Title from spine.
Keywords: Art, Maori -- 21st century -- Exhibitions; Art, New Zealand -- Catalogs; Art, New Zealand -- 21st century -- Exhibitions; Artists, Maori